Given C_1->y^2+x^2-4x-6y+9=0C1y2+x24x6y+9=0, C_2->y^2+x^2+10x-16y+85=0C2y2+x2+10x16y+85=0 and L_1->x+2y+15=0L1x+2y+15=0, determine C->(x-x_0)^2+(y-y_0)^2-r^2=0C(xx0)2+(yy0)2r2=0 tangent to C_1,C_2C1,C2 and L_1L1?

1 Answer
Sep 5, 2016

There are two solutions as explained below.

Explanation:

Firstly we will represent the geometric objects in a more convenient formulation.

So

C_1->y^2+x^2-4x-6y+9=0C1y2+x24x6y+9=0 for
C_1->(x-x_1)^2+(y-y_1)^2=r_1^2C1(xx1)2+(yy1)2=r21
C_2->y^2+x^2+10x-16y+85=0C2y2+x2+10x16y+85=0 for
C_2->(x-x_2)^2+(y-y_2)^2=r_2^2C2(xx2)2+(yy2)2=r22
L_1->x+2y+15=0L1x+2y+15=0
L_1->p = p_3+lambda_3 vec v_3L1p=p3+λ3v3

After reduction, we have

p_1=(2,3), r_1=2p1=(2,3),r1=2
p_2=(-5,8), r_2=2p2=(5,8),r2=2
p_3=(-15,0), vec v_3 =(1,2)p3=(15,0),v3=(1,2)

Now, given

C_1->norm(p-p_1) = r_1C1pp1=r1
C_2->norm(p-p_2)=r_2C2pp2=r2 and
L_1->p_3+lambda vec v_3L1p3+λv3

find

C->norm(p-p_0) = r_0Cpp0=r0

such that

C is tangent to C_1,C_2and L_1

Here p = (x,y) and p_0=(x_0,y_0)

We can stablish the following retationships

norm(p_0-p_1)=r_0+r_1
norm(p_o-p_2)=r_0+r_2

if p_t in L_1 is a tangency point then

<< p_t-p_0, vec v_3 >> = 0
norm(p_t-p_0)= r_0

where

p_t = p_3+lambda vec v_3

Finally we get the following equations

{ (<< p_3+lambda vec v_3-p_0,vec v_3 >> = 0), (norm(p_3+lambda vec v_3-p_0)=r_0), (norm(p_0-p_1)=r_0+r_1), (norm(p_0-p_2)=r_0+r_2) :}

so we have four equations and four incognitas x_0,y_0,lambda,r_0

Solving we obtain

((r_0 = 8.17665, x_0 = -6.86077, y_0 = -2.00508, lambda = 0.825813), (r_0 = 11.6327, x_0 = 6.01912, y_0 = 16.0268, lambda = 10.6145))

Attached the figure with the solutions in red and the initial geometric elements in black.

enter image source here